The Impact Of Digitalization On Shipping Logistics and Supply Chain Management - Damar Pranaja Wijaya; Bagas Raditya (Indonesian Maritime Researchers and Lecturers, 2025)
The rapid advancement of digital technologies has significantly transformed the shipping logistics and supply chain management sectors. This study explores the impact of digitalization on these industries, focusing on the integration of technologies such as artificial intelligence, blockchain, and the Internet of Things (IoT). The primary objective of this research is to analyze how digital tools enhance operational efficiency, reduce costs, and improve decision-making in logistics and supply chain operations. Through qualitative and quantitative methods, including case studies and surveys, the study identifies key trends and challenges faced by organizations adopting these technologies. Findings reveal that digitalization leads to improved transparency, real-time tracking, and enhanced collaboration across the supply chain. However, challenges such as cybersecurity risks, high implementation costs, and the need for skilled labor remain significant. The implications of these findings suggest that while digital transformation offers considerable benefits, organizations must carefully manage the transition to ensure sustainability and long-term success.